Two new species of the aphid genus Uroleucon (Hemiptera: Aphididae) living on Grindelia in the USA - Barjadze, Shalva; Kanturski, Mariusz (European Journal of Taxonomy, 2020)
Here, we present descriptions of two new aphid species of the genus Uroleucon Mordvilko, 1914 (Hemiptera: Aphididae: Macrosiphini), which are associated with the plant genus Grindelia Willd. (Asteraceae). An apterous viviparous female of Uroleucon (Lambersius) robinsoni sp. nov. from Oregon and apterous and alate viviparous females of Uroleucon (Lambersius) grindeliae sp. nov. from Colorado are described and illustrated. Taxonomical notes of the new and other Grindelia-feeding taxa of Uroleucon are given and an updated key to the apterae of the Grindelia-feeding species of Uroleucon in the world is provided.